2018
DOI: 10.3390/w11010031
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the Urban Expansion Effects on the Design Storm Hydrograph and Sediment Yield Using Artificial Neural Networks

Abstract: Urban expansion substantially alters the impervious areas in a catchment, which in turn affects surface runoff and sediment yield in the downstream areas. In this study, the Land Transformation Model (LTM) was used to forecast the urban land expansion in a catchment, whilst future land use maps were employed according to the Soil Conservation Service Curve Number method (SCS-CN) and the Modified Universal Soil Loss Equation (MUSLE) model, so as to examine the urbanization effects on runoff and sediment yield p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 57 publications
1
27
0
Order By: Relevance
“…Additionally, Segura-Beltrán et al [13] analyzed the flash flood of the Girona River (Spain) in 2007 and found that some human-induced factors, such as artificially narrow stream width, walls, and roads, caused the overbank flow. Similar findings from other researches [12,36,[60][61][62][63] in watersheds very close to the study area (Chalkidiki region) showed the significant influence of…”
Section: Discusion On Flood Generation Causessupporting
confidence: 90%
“…Additionally, Segura-Beltrán et al [13] analyzed the flash flood of the Girona River (Spain) in 2007 and found that some human-induced factors, such as artificially narrow stream width, walls, and roads, caused the overbank flow. Similar findings from other researches [12,36,[60][61][62][63] in watersheds very close to the study area (Chalkidiki region) showed the significant influence of…”
Section: Discusion On Flood Generation Causessupporting
confidence: 90%
“…One major problem faced by water engineers is the determination of the most suitable form of an extreme value model, the underlying probability distribution of the flood, and the approximation of parameters of the distribution. Specifying the frequency of occurrence of the possible values of a random variable through probability distribution is of immense importance for the planning, engineering design, and management of water systems and hydraulic structures, including drought hazards, urban planning, growth forecasting [7], agrosystem management, and environment ecosystem management in river basins.…”
Section: Introductionmentioning
confidence: 99%
“…Such an approach could improve the quality of the dataset and enhance the accuracy of estimation methods, which should be enhanced with a statistical approach [2,4].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Over the past several decades, increasing development in coastal cities has been highlighted as one of the major factors of flood damage [1]. Not only do typhoons and heavy rains occur frequently [2], also, urban development that leads to unprecedented severe flood damage has increased [3,4]. For urban planning in particular, public resources have been devoted to building public facilities for urban development [1].…”
Section: Introductionmentioning
confidence: 99%